ESBL and MBL in Cefepime Resistant Pseudomonas aeruginosa: An Update from a Rural Area in Northern India - Kotwal, Aarti (J Clin Diagn Res, 2016)
INTRODUCTION: Cefepime, a fourth generation cephalosporin, is widely used for the empirical treatment of serious infections in critically ill hospitalized patients. Pseudomonas aeruginosa (P. aeruginosa), one of the commonest bacteria causing nosocomial infections has a propensity to develop antibiotic resistance quite promptly. AIM: We undertook this study to assess the efficacy of cefepime against current clinical isolates of P. aeruginosa and to study existence of different beta-lactamase enzymes among cefepime resistant P. aeruginosa isolates. MATERIALS AND METHODS: Total of 618 isolates of P. aeruginosa recovered consecutively from various clinical samples of a tertiary care hospital were analysed. Their Antimicrobial sensitivity profile against piperacilin (100μg), piperacillin/tazobactam (100μg/10μg), ceftazidime (30μg), cefoperazone (75μg), cefepime (30μg), ciprofloxacin (5μg), gentamycin (10μg), amikacin (30μg) and imipenem (10μg) (Himedia) was tested by Kirby-Bauer disc diffusion method (Clinical and Laboratory Standards Institute guidelines). We further looked for ESBL, MBL and ESBL + MBL co producers among the cefepime resistant isolates by two different methods (combined double disc synergy test, imipenem-EDTA combined disc test and vitek2). RESULTS: Among 618 consecutive clinical isolates of P. aeruginosa, we observed resistance to cefepime in 457 (74%) isolates. We observed resistance to ciprofloxacin (n=506, 82%) in maximum number of isolates followed by that to Gentamycin (n=475, 77%), amikacin (n=366, 60%), and cefoperazone (n=350, 56.6%). Among all our cefepime resistant P. aeruginosa isolates only 27(6%) were ESBL producers, 18(4%) MBL producers and 2(0.4%) were ESBL+ MBL co-producers. All the ESBL and MBL isolates were also tested by VITEK 2 advanced expert system (bioMırieux Vitek Systems Inc, Hazelwood, MO, France) which revealed a 100% concordance with the phenotypic method tested. CONCLUSION: This paper highlights the need to reconsider prescribing empirical antibiotics for Pseudomonas infections in this region and formulate a strong antibiotic policy to curb the menace of spread of multidrug resistant strains.